Handbook on the economics of sport - Andreff, Wladimir 1946-; Szymanski, Stefan 1960- (Cheltenham [England] Edward Elgar, 2009)
This handbook presents a survey of all the major research areas in sports economics. It offers an insight into the major findings of the literature as well as researchers' views on some of the questions remaining to be answered.
Introduction : Sport and economics / Wladimir Andreff and Stefan Szymanski -- Sports accounting / Wladimir Andreff -- The production of professional team sports / Jeff Borland -- The sports goods industry / Wladimir Andreff -- Sport and gambling / David Forrest -- Sponsorship / Claude Jeanrenaud -- International trade in sports goods / Wladimir Andreff -- The demand for sport / Jean-Jacques Gouguet -- The demand for spectator sports / Rob Simmons -- Attendance at sports events / Patrick Feehan -- The demand for sports broadcasting / Babatunde Buraimo -- The demand for media coverage / Frédéric Bolotny and Jean-François Bourg -- Economic impact analysis / Victor Matheson -- Physical activity, sport and health / Jean-François Nys -- Employment in sport / Didier Primault -- Sporting externalities / Jean-Jacques Gouguet and Eric Barget -- The economic impact of mega-sporting events / Robert A. Baade -- The Olympics / Holger Preuss -- The World Cup / Markus Kurscheidt -- The economic impact of sporting facilities / Brad R. Humphreys -- Voluntary work in sport / Wladimir Andreff -- Governance and governing bodies in sport / Thomas Hoehn -- The economics of the IOC / Jean-Loup Chappelet -- Government objectives and sport / Barrie Houlihan -- Central government and sport / Jean-François Nys -- Sport and financing / Wladimir Andreff -- Military sport / Jean-François Nys -- Local government and regional development in sport / Carlos Pestana Barros -- The European model of sport / Peter J. Sloane -- The Anglo-American model of sport / Stefan Szymanski -- Sport in developing countries / Wladimir Andreff -- Soviet and post-Soviet sport / Sandrine Poupaux -- International labour migration / Wladimir Andreff -- Comparative advantage of nations / Wladimir Andreff -- The theory of tournaments / Stefan Szymanski -- Implications from the theory of contests for modelling and designing sports competitions / Gerd Muehlheusser -- Citius, altius, fortius : the production of world records in the running and technical disciplines in track and rield / Bernd Frick, Joachim Prinz and Frank Tolsdorf -- On the competitive structure in professional boxing, or, why the best boxers very seldom fight each other / Rafael Tenorio -- Golf / Chantelle Bramley -- The economics of British horseracing / Wray Vamplew -- The economics of collegiate athletics / Karl W. Einolf -- The economics of US intercollegiate sports and the NCAA / Robert Sandy -- The economics of cycling / Michel Desbordes -- Extreme sports (climbing and mountaineering) / Gilles Rotillon -- The economics of tennis / Eric Barget -- The development of team sports before 1914 / Wray Vamplew -- Organisational models of professional team sports leagues / Andrew Zimbalist -- Baseball economics / Stefan Szymanski -- The economics of soccer /A John Goddard -- Football in England / Stefan Szymanski -- The state of the Italian football industry / Umberto Lago -- The economics of soccer in Spain / Jaume García and Plácido Rodríguez -- Football in Germany / Bernd Frick -- Football in France / Frédéric Bolotny -- American football / Michael Leeds -- Labour economics on the hardwood : the NBA / David J. Berri -- European professional basketball in crisis, 1992-2002 / Didier Primault -- Ice hockey / Marc Lavoie -- The economic development of the Australian Football League / Ross Booth -- Rugby : strategy and structure / John McMillan -- The economics of professional rugby / Pierre Chaix -- The economics of cricket / Ian Preston -- Uncertainty of outcome, competitive balance and the theory of team sports / Stefan Szymanski -- The objective function of a team / Stefan Késenne -- Production functions for sporting teams / Jeff Borland -- Revenue sharing / Stefan Szymanski -- The reserve clause in major league baseball / Lawrence Hadley -- The retain and transfer system / Dennis Thomas -- The Bosman case and European football / Stefan Késenne -- The reverse-order-of-finish draft in sports / Leo H. Kahane -- Chasing the elusive salary cap / Daniel R. Marburger -- The luxury tax in professional sports / Elizabeth Gustafson -- 'At the top table' : player unions in soccer / Braham Dabscheck -- The player transfer system in soccer / Fiona Carmichael -- Player agents / Daniel S. Mason -- The promotion and relegation system / Stefan Szymanski -- Team sports and finance / Wladimir Andreff -- Inelastic sports pricing at the gate? : a survey / Rodney Fort -- Financial innovation in professional team sports : the case of English Premiership soccer / Bill Gerrard -- Collective selling of broadcast rights in team sports / Susanne Parlasca -- The sporting exception and the legality of restraints in the US / Stefan Szymanski -- The specificity of sport and the European Community law : the example of nationality / Jean-Christophe Breillat and Frank Lagarde -- Sport and globalisation : sport as a global public good / Jean-François Bourg and Jean-Jacques Gouguet -- Racial discrimination / Neil Longley -- Gender discrimination / Brad R. Humphreys -- Doping / Nicolas Eber -- Corruption / Wolfgang Maennig.
Originally published: 2006.
Keywords: Sports -- Economic aspects; Professional sports -- Economic aspects